2022
DOI: 10.3390/antibiotics11121786
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Beta-Lactam Allergic and Non-Beta-Lactam Allergic Patients with Intra-Abdominal Infection: A Case–Control Study

Abstract: Background: In the case of intra-abdominal infections (IAI) in beta-lactam (BL) allergic patients, empiric antimicrobial therapy without BL is recommended; however, data regarding the outcome with alternative regimens are scarce. This study aimed to compare the outcomes of BL allergic (BLA) patients with IAI to those who were non-BLA (NBLA). Method: We conducted a case–control study in a French teaching hospital, between 1 January 2016 and 31 August 2021. BLA patients with IAI treated with fluoroquinolone or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…While awaiting new antimicrobial therapeutic innovations, some authors have suggested the systematic use of antibiotics effective against biofilm [ 7 ]. Fluoroquinolones, in particular, levofloxacin and moxifloxacin, which have the lowest minimum inhibitory concentrations for enterococcal species, have been proposed, but data on their use for the treatment of enterococcal infections are scarce [ 22 , 23 ]. Rifampicin-based combination therapy has been reported to be associated with better outcomes [ 8 ]; however, our study did not confirm this result ( Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…While awaiting new antimicrobial therapeutic innovations, some authors have suggested the systematic use of antibiotics effective against biofilm [ 7 ]. Fluoroquinolones, in particular, levofloxacin and moxifloxacin, which have the lowest minimum inhibitory concentrations for enterococcal species, have been proposed, but data on their use for the treatment of enterococcal infections are scarce [ 22 , 23 ]. Rifampicin-based combination therapy has been reported to be associated with better outcomes [ 8 ]; however, our study did not confirm this result ( Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%